Investigation of the Effects of Probiotics on Sub-Chronic Neonicotinoid Toxicity in Rats - Sevim, Cigdem; Akpinar, Erol; Tsatsakis, Aristides; Yildirim, Serkan; Tzatzarakis, Manolis; Vardavas, Alexander I.; Vardavas, Constantine I.; Kara, Mehtap; Gul, Zulfiye (MDPI AG, 2021)
Probiotics have been shown to have positive effects when it comes to combating various health issues when consumed, preventing even the absorption of environmental toxins. One of the main environmental toxins encountered today is pesticide residues. Neonicotinoids, widely applied today in countries that have approved of them, are a known class of insecticides with an excellent and effective potency. Neonicotinoids have been shown to cause various toxic effects, either acutely or chronically, on human health and on beneficial insects when exposed. To clarify the assumption that probiotics could counteract these toxic effects, especially on vital organs, the probiotic yeast “Saccharomyces boulardii” (S. boulardii) was tested against the neonicotinoids, acetamiprid (ACE) and imidacloprid (IMI), as it has outstanding physiological and metabolic properties. The results obtained from the studies indicated that although ACE and IMI induced liver, kidney, brain and bowel damage, there was a considerable level of protection by the dietary supplementation of S. boulardii, as it reduced the absorption of these insecticides.
Keywords: probiotics; S; acetamiprid; neonicotinoid; Agriculture; imidacloprid; Saccharomyces boulardii; 3. Good health